Emerging Trends in Children's Aesthetic Anterior Crowns (International Journal of Food and Nutritional Sciences, 2022)
Children who lose their anterior teeth may experience aesthetic issues, neuromuscular imbalance with reduced masticatory efficiency, speech problems, the emergence of parafunctional habits, and psychological issues. There is a higher demand for treatments for ugly issues like caries, stained teeth, hypoplastic abnormalities, fractures, and missing teeth in youngsters as people become more aware of the cosmetic options available. The largest challenge, though, is deciding which therapy option is best for a given patient and circumstance. As a result, this review outlines the numerous recent developments in the field of anterior crowns in paediatric cosmetic dentistry, as well as their applications, benefits, and drawbacks.